The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1542/peds.2020-1853
|View full text |Cite
|
Sign up to set email alerts
|

The Revised WIC Food Package and Child Development: A Quasi-Experimental Study

Abstract: BACKGROUND AND OBJECTIVES: The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), one of the largest US safety net programs, was revised in 2009 to be more congruent with dietary guidelines. We hypothesize that this revision led to improvements in child development. METHODS: Data were drawn from a cohort of women and children enrolled in the Conditions Affecting Neurocognitive Development and Learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…For instance, prior studies have found that the revision led to improvements in proximal outcomes including dietary quality and access to healthy foods [6,9]. Additionally, a smaller number of studies have looked at perinatal health in sub-national samples [14][15][16]. As a specific example, one previous study found positive improvements in gestational weight gain following the revision [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, prior studies have found that the revision led to improvements in proximal outcomes including dietary quality and access to healthy foods [6,9]. Additionally, a smaller number of studies have looked at perinatal health in sub-national samples [14][15][16]. As a specific example, one previous study found positive improvements in gestational weight gain following the revision [14].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we evaluated change in parent-reported health similar to the question for adults described above. Finally, results from a systematic review suggest that improvements to overall dietary quality led to improvements in mental health for children [ 31 ], while another study found that the 2009 WIC revision improved child development outcomes among recipient children [ 16 ]. Therefore, we additionally evaluated changes to children’s mental health, which was measured for children aged 2–3 years with the Mental Health Indicator (MHI) score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] Research on health outcomes has been limited, with a handful of studies finding that the revised WIC program improved maternal and child dietary quality, [25][26][27][28] GWG, infant birth weight, and measures of child growth and development. [29][30][31] Select studies involved rigorous, quasiexperimental designs, but used small samples or narrow geographies. Further research is needed to evaluate the effects of the revised WIC program in a more generalised sample to inform national policymaking.…”
Section: Department Of Agriculture Enacted Major Revisions To the Wicmentioning
confidence: 99%
“…Prior studies have found that the revised WIC program was associated with increased availability of healthy foods at neighbourhood stores 19,20 and increased household expenditures on healthy foods 21–24 . Research on health outcomes has been limited, with a handful of studies finding that the revised WIC program improved maternal and child dietary quality, 25–28 GWG, infant birth weight, and measures of child growth and development 29–31 . Select studies involved rigorous, quasi‐experimental designs, but used small samples or narrow geographies.…”
Section: Introductionmentioning
confidence: 99%